وظائف الدولة الإسلامية = The duties and function of an Islamic state - Mohd Nor, Amir Husin; Mustafa, Abd Wadud; Laluddin, Hayatullah; Muhammad Husni, Ahmad; Ibrahim, Ibnor Azli; Samsudin, Mohd Adib; Omar, Anuar Fahri; Alias, Muhammad Nazir (Institut Islam Hadhari, Universiti Kebangsaan Malaysia (UKM), 2012)
Islamic state has always been the focal of political analysis and is viewed by some people as the essence of the study of political science. Therefore, it is necessary in any study concerning state to discuss its duties and functions. For state regardless of its contents, throughout different epochs of history and through different models attempts to achieve certain duties, which are determined by political doctrines and ideologies. The existence of difference as regards to the duties and functions of the state is an evidence of the pivotal role of the political doctrine and ideologies in the state. Therefore, we can safely say that the contents and different dimensions of state duties are greatly influenced by some universal doctrine which decide its direction locally and internationally. Thus, state can be considered as a social instrument or means for the realization and establishment of political doctrines and ideologies, which represent the justifying ground for its legality and functions. This paper attempts to deliberate on the functions and duties of Islamic state as perceived by classic and contemporary scholars.